Female board representation and board risk committee / Sharifah Faatihah Syed Mohd Fuzi, Mohamat Sabri Hassan and Noorie Haryaniee Moulton - Syed Mohd Fuzi, Sharifah Faatihah; Hassan, Mohamat Sabri; Moulton, Noorie Haryaniee (2021)
The board of directors is mainly responsible for effective internal control and risk management. One of the reasons for the global financial crisis was the director's lack of time commitment, resulting in excessive risk-taking (Iselin, 2020). Hence, policymakers, regulators, and stakeholders demand firms to establish a board risk committee (Aljughaiman & Salama, 2019; Ames et al., 2018). Before the global financial crisis, the audit committee was in charge of risk oversight functions. However, the audit committee's responsibility for risk oversight has been called into doubt due to business failure (Malik et al., 2021). Both committees also have distinct responsibilities. Whilst, board risk committee is responsible for identifying risks and managing or mitigating them as effectively as possible (Ames et al., 2018). Meanwhile, the audit committee oversees risk oversight, which includes overseeing the external audit's function (Iselin, 2020). Besides, delegating risk supervision responsibility to the separate committee, such as the board risk committee considered costly (Ames et al., 2018). It necessitates greater time commitment and resources (Iselin, 2020). Therefore, it is subject to the board's discretion in setting up the committee. This study expects female corporate board members to influence the board's decision, especially in establishing a board risk committee. Prior studies have discussed the implications of female board representation on firm behaviour and performance. However, there is still inconclusive evidence to support the effective functions of having female directors. For instance, there is no evidence of female directors' influence on firm value and profitability in Turkey unless they can provide an active role in the board committee (Ararat & Yurtoglu, 2021). Even female directors adversely affect Islamic banks globally (Khan et al., 2020). Nonetheless, it is suggested that female directors can provide valuable insight into governance practices when they are involved in board committees. By using a sample of Omani financial companies, female members in the audit committee can improve forward-looking disclosure quality (Lawati et al., 2021). Further, the gender-diverse audit committee was found to reduce aggressive tax practices (García-Meca et al., 2021). The rationale for having female board representation is to increase independence, broaden valuable resources such as expertise and provide efficient monitoring (Lawati et al., 2021). Despite the growing concern on the female directors' function and board risk committee, there is still a limited number of empirical evidence that examine the influence of female directors on the board risk committee. Thus, this study aims to examine to what extent that female board representation influences the board risk committee.